Здесь водятся чудовища: Фантаст. романы: перевод с английского / А. Нортон - Нортон Андрэ (Стальная Крыса, 2006)
Экземпляры: Ф. 13 (20230309) / Инвентарный номер: 49770 / Цена: 25.00 / Авт.знак: Н83 / ББК: 84(7Сое)